The child as a social actor - critiques, counter-arguments and theoretical and empirical challenges (Práxis Educativa, 2017)
This paper discusses the theoretical and empirical challenges of the idea of the child as a social actor, present in the social studies of childhood, through the analysis of criticisms made to the concept by authors belonging to the field and authors external to it. Counter-arguments are also discussed in its defense. The criticisms and counter-arguments extend over a period of 10 years (2005 to 2015). The concept of social actor is situated in this paper in the bias of the weberian theory and in the framework of the ‘double hermeneutic’ as A. Giddens’s ‘model of reflexivity’ in social sciences: theorizing about the phenomenon implies being involved in its contemporary process of deconstruction/reconstruction. Thus, the risks or consequences of what science claims about children will fall on themselves and on the social forms of their understanding. In this sense, it is understood that the alerts made to the specialist discourse (both the critical discourse and the critical defense of the concept) must be analyzed. Keywords: Child. Social actor. Social studies of childhood.